Penyuluhan Pencegahan Bahaya Listrik dan Petir pada Instalasi Listrik Rumah Tangga di Lembang Dewata Kecamatan Mappak Kabupaten Tana Toraja - Syahir Mahmud (Gapenas Publisher, 2022)
Tana Toraja Regency as one of the national tourist destinations within the administrative area of South Sulawesi Province. Tana Toraja Regency, which has a city in Makale, is located at 3°06'17